Forensic Profiling Analogue Approach for the Investigation of Natural Hazards – A Case Study from Onokoba Elementary School, Unzen Volcano, Japan - Christopher Gomez; Yoshinori Shinohara; Norifumi Hotta; Balázs Bradák (Universitas Muhammadiyah Surakarta, 2021)
Internal temperature variations of pyroclastic flows and their deposits are arguably the most challenging data to acquire. As a preliminary study of the temperature variation inside pyroclastic flows, the remains of Onokoba Elementary School (Shimabara, Japan) were investigated. The elementary school is located in the close vicinity of Unzen volcano and was hit by one of the largest pyroclastic flows during the latest active period of the volcano on 15th of September 1991. This present preliminary study aims to determine the temperature exposure of various portion of the school building using field-forensic and urban geology. Natural hazard methods applied to the damaged materials exposed to high temperature have generated a temperature fingerprint the maximum temperature distribution. Charred wooden parts and plastic gutters installed on the schoolyard-side faced of the building turns out to be the most useful temperature indicators. The various deformation and alterations of the studied materials show significant differences in the temperature exposed to. Such differences on the second-floor section (between 75-110°C and 120-150°C) and on the first-floor section (above 435-557°C) of the building do not simply imply significant temperature heterogeneity in short distance (some ten to ≤100 m) inside the pyroclastic flow, but also points toward the possible effects of the building architecture on some key dynamic parameter of the pyroclastic flow. Such information may be important for planning future hazard mitigation actions.